The mechanical and durability properties of high strength concrete sleeper with steel slag as partial cement and sand replacement - Li, Xiaofeng (2024)
Concrete is one of the most widely used civil engineering material since it has good mechanical property which is essential requirement for construction/infrastructure development. Steel slag has been regarded as an alternative material to replace cement and/or sand for making concrete for the perspective of potential economic benefits and reduction in environmental hazards. Previous studies have been conducted on investigating the effect of addition of SS powder or SS sand on performance of concrete, while there is not effort has been made on studying the combined use of SS powder and SS sand for producing high strength concrete. In this study, SS powder was used as cement replacement and SS sand was used as partial sand replacement to produce HS-SSCSC and HS-SSCSC sleeper. At the beginning of the study, trial mix was conducted to determine the content of cement, fine aggregate, coarse aggregate, superplasticizer, water and replacement ratio of SS sand. SS powder was added with replacement ratio of 0, 10%, 20%, 30% and 40% to replace cement. To investigate the effect of the addition of SS powder and SS sand on the mechanical properties and durability properties. The mechanical property tests consist of compressive strength test, flexural strength test, splitting tensile strength test, modulus of elasticity test. Durability property tests consist of resistance to acid attack test, resistance to sulfate attack test, water absorption test. Part of the concrete samples were conducted thermogravimetric analysis and scanning electron microscopy with energy dispersive X-ray spectroscopy test. The five concrete mixes were used to manufacture HS-SSCSC sleeper. To evaluate the structural behavior of HS-SSCSC sleeper, few tests were performed, including static load test, vibration characteristics, crack distribution and propagation. Results showed that 550 kg/m3 cement, 600 kg/m3 fine aggregate, 1100 kg/m3 coarse aggregate, 0.34 water-cement ratio, 1.3% superplasticizer and 30% SS sand could be selected as optimum content for making control mix. the addition of 10% SSP has positive effect on HS-SSCSC compressive strength, flexural strength, splitting tensile strength and modulus of elasticity. 10% HS-SSCSC achieved the highest residual compressive strength compared to HS-SSCSC with other SSP replacement ratio after exposed to 5% hydrochloric acid solution. Meanwhile, 10% HS-SSCSC still kept the highest compressive strength compared to HS-SSCSC with other SSP replacement ratio after exposed to 5% sodium sulfate solution. The 10% HS-SSCSC has the lowest water absorption within 24 hours compared to other mixes. The weight loss of HS-SSCSC with 0% and 10% SSP replacement ratio have similar trend at 7-day, 28-day, 90-day, 180-day and 365-day. The concrete possesses higher compressive strength and flexural strength will lead to the higher stiffness in HS-SSCSC sleeper at center part. The concrete possesses higher compressive strength and splitting tensile strength will lead to the higher stiffness in HS-SSCSC sleeper at rail-seat part. The resonant frequency of HS-SSCSC sleeper at each mode was corresponding to the mechanical properties of HS-SSCSC. HS-SSCSC sleeper manufactured with different concrete mixes exhibited different features on exergy dissipation at various mode. Two vibration modes, which were bending mode and torsional mode, were detected on the vibration test. The initiation of crack generation corresponds to the mechanical properties of HS-SSCSC, and the cracks tended to branch at certain load level. In conclusion, the combination of SSP and SS sand for producing HS-SSCSC is feasible and has positive influence on mechanical and durability properties of HS-SSCSC. The HS-SSCSC can also be used for manufacturing HS-SSCSC sleeper, which achieves good structural performance.